(untitled) (Web of Teachers: Inderscience Research, 2025)
This paper discusses the impact of language on human beliefs from a psycholinguistic perspective. It looks into psychological and linguistic processes—such as framing, word selection, emotional words, and repetition—that turn persuasive language into an effective tool. The paper also points out the ways in which slight variations in speech can color perception, opinion, and decision-making, and why awareness of the ethical effects of persuasive communication is important.